Fansubbing Korean audiovisual pop cultural works: a case study of the (in)visibility of online translators of “Running man” in Vietnam = Nghiên cứu điển hình về tính hữu hình của các nhóm dịch chương trình “Running man” trên mạng Internet - Nguyễn, Quỳnh Mai (2021)
This study was set out to examine the (in)visibility of two subtitle translation teams of a Korean audiovisual pop cultural work – “Running Man”, with the objective of identifying whether both teams are visible or not to the audience. In order to comply with the objective, a theoretical framework was adopted to assess translator’s (in)visibility; and the opinion of “Running Man” audience was also consulted. To be more specific, in order to gather necessary data for the research, different documents (including the subtitles and videos of “Running Man”) were collected for observation, and a questionnaire was delivered to collect the audience’s opinion about the matter. The results from content and statistical analysis revealed that the two examined translation teams were visible to the audience based on both the framework and the audience’s opinion. Moreover, as compared to the framework and perceived by the audience, there are four criteria constituting the translator’s visibility: (1) the presence of the teams’ name or logo in their translation, (2) the application of foreignisation strategy in culture-specific items, (3) interaction between the teams and their audience, and (4) the quality of their released video.